Development of powdered kombucha sourdough starter culture and characterization of kombucha sourdough bread - Mohd Roby, Bizura Hasida (2020)
Sourdough bread has gained consumer interest due to its excellent sensory characteristics and health functions. However, sourdough starter culture preparation for breadmaking is very tedious, and the inconvenience of liquid traditional sourdough starter (LTSS) culture is not preferred in the modern lifestyle. Therefore, this research was conducted to optimise the production of liquid kombucha sourdough starter (LKSS) culture using Response Surface Methodology (RSM), to evaluate the effect of gum Arabic (GA) on the properties of encapsulated kombucha sourdough starter (EKSS) culture powder, and to characterize the properties of sourdough bread prepared using the EKSS culture. RSM was applied to optimise the incubation temperature (31-37ᴼC) and refreshment time (every 8-12 hours) of LKSS culture production, to minimise the ripening time (h) and maximise the leavening rate (mL/h). The LKSS culture produced at its optimum conditions was compared with the LTSS culture for the microbiological properties and metabolomics profiling using 1H-NMR based technique. The LKSS culture was transformed into powder via encapsulation using GA and spray drying. The EKSS culture properties were evaluated compared to the unencapsulated kombucha sourdough starter (UKSS/control) culture. The powders were stored at different storage to investigate the culture viability throughout 3 months of storage. The EKSS culture was used in breadmaking, and the bread properties were compared with LTSS and baker’s yeast (BY) bread. RSM optimisation revealed the optimised incubation temperature and refreshment time for the LKSS culture production are at 34ᴼC and every 7 hours, respectively. The LKSS culture showed significantly (p<0.05) higher lactic acid bacteria (LAB) (11.07±0.04 log10CFU/g) and yeast (10.37±0.05 log10CFU/g) counts compared to LTSS. The 1H-NMR analyses showed the presence of 15 metabolites in LKSS culture. The major compounds contributing to LKSS culture's differences were alpha-aminobutyric acid, alanine, acetic acid, riboflavin, pyridoxine, anserine, tryptophan, gluconic acid, and trehalose. GA was found adequate to produce EKSS culture with significantly (p<0.05) lower moisture content (5.20±0.19%) and water activity (0.32±0.02), higher LAB (9.93±0.10 log10CFU/g) and yeast (9.40±0.15 log10CFU/g) viability and survival percentage (90.27% for LAB and 89.52% for yeast) after spray drying compared to control. EKSS culture was stable at 27-29ᴼC as high microbial viabilities for 2 months of storage were observed. EKSS culture extract also exhibited high antibacterial activity (>85% inhibition) against pathogenic and spoilage bacteria used in this study. EKSS culture has produced bread with significantly higher loaf volume (976.70±25.2mL) and specific loaf volume (4.38±0.12mL/g), lower pH (5.16±0.02), longer storage life (6 days), and lower crumb firmness (116.07±6.28g) than BY bread. EKSS culture bread inoculated with spoilage fungi delayed the mycelia growth to 5–10 days compared to BY bread. EKSS culture bread extract demonstrated significantly (p<0.05) higher antibacterial activity (50±0.07 to 100±0.00%) than BY bread extract. EKSS culture bread had significantly (p<0.05) higher taste and overall acceptability scores than BY bread, indicating this bread was well accepted by consumers. The findings showed that the EKSS culture promises to produce functional sourdough bread with extended shelf life and improved quality that could greatly benefit the bread industry.